High purity fructose from inulin with heterogeneous catalysis – kinetics and modelling. Issue 1 (20th July 2017) - Pérez Nebreda, Andrea; Salmi, Tapio; Murzin, Dmitry Yu; Grénman, Henrik
Abstract: BACKGROUND: Inulin can be extracted from the non‐edible chicory root and high purity fructose can be obtained from hydrolysis of inulin and used as a valuable platform molecule for further valorization. Heterogeneous catalysts are sought as alternatives to mineral acids because of costly separation and severe corrosion problems. In this work, hydrolysis of inulin was performed in a batch reactor with an advanced sulfonic resin (Smopex‐101) employing HCl as a reference catalyst, at 75–95 °C and pH ranging from 1 to 2. RESULTS: The reaction was shown to proceed predominantly via an end‐biting mechanism. The activity of the heterogeneous catalyst was on par with the reference catalyst, with the special advantage that Smopex‐101 was more selective towards monomer formation at milder reaction conditions. Mathematical modelling of the kinetics was successfully performed with a recently developed model incorporating a reaction mechanism based on an autocatalytic effect. CONCLUSIONS: The current work demonstrates that high purity fructose can be obtained by hydrolysis of inulin employing a heterogeneous catalyst at ambient pressure. The results can be utilized directly for optimization and design purposes and they open up novel possibilities in production and process design, i.e. batch or possibly continuous operation without the need for costly separation and corrosion problems commonly encountered with homogeneous catalysts. © 2017 Society of Chemical Industry